Interview with education inspector D. Carlos Utrera Infantes - Editorial, Equipo (Avances en Supervisión Educativa, 2019)
Carlos Utrera has been an education inspector since 1989 and throughout his career he has held positions of responsibility in the Educational Inspection Services of Cantabria and Madrid. He has also been president of the Association of inspectors of Madrid and president of ADIDE-Cantabria.Since 2015 he has served as president of ADIDE-Federation. He has been the eleventh president and under his mandate the last two national congresses of Valladolid and Bilbao have been developed. In October of this year 2019, he did not show up for the renovation and gave way to Lourdes Oureta Mendía, president of the association of inspectors education of the Basque Country.
Keywords: Interview